Curriculum Management In The Formation Of Student Eco-Student Character In Jarinabi Islamic Junior High School - Adi Mulyono; Ngantori (Universitas Muhammadiyah Enrekang, 2026)
The formation of environmental care character in students is one of the challenges in the world of education, especially in the management of a curriculum that has not fully integrated environmental values systematically. Therefore, the concept of eco-restraint is one of the approaches that can be applied in curriculum management to instill ecological awareness in students. This study aims to analyze curriculum management in the formation of student eco-student character at Jarinabi Islamic Junior High School. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that curriculum management in the formation of eco-student character is carried out through the planning, implementation, and evaluation stages of curriculum that are integrated with learning activities and school environmental programs. The implementation of the curriculum has a positive impact on the formation of students' character, especially in fostering an attitude of environmental care, responsibility, and discipline. The implications of this study show that the management of an eco-learning-based curriculum can be an effective strategy in supporting the formation of environmentally conscious students' character.